Some δ-Tempered Fractional Hermite–Hadamard Inequalities Involving Harmonically Convex Functions and Applications - Nousheen Akhtar; Muhammad Uzair Awan (Journal of Mathematics)
The main objective of this paper is to obtain some new δ-tempered fractional versions of Hermite–Hadamard’s inequality using the class of harmonic convex functions. In order to show the significance of the main results, we also discuss some interesting applications.